Historical and post-ban releases of organochlorine pesticides recorded in sediment deposits in an agricultural watershed, France. (1st November 2021) - Gardes, Thomas; Portet-Koltalo, Florence; Debret, Maxime; Copard, Yoann
Abstract: Agricultural use of organochlorine pesticides (OCPs) increased during the twentieth century but many of them have been progressively banned several decades after their introduction. Nevertheless, these lipophilic chemical compounds may persist in soils and sediments. From sediment deposits, it is possible to reconstruct the chronology of OCP releases in relation to former applications through time. Nevertheless, long-term fate of OCPs i.e. source, transfer, and storage through the watershed, is also related to the OCPs-sediment characteristics interactions, and our study showed the significant links between OCPs and labile or refractory organic matter. From sediment cores collected in a mainly agricultural watershed, the Eure River watershed (France), aldrin and lindane widespread applications during the 1950s–1970s have been recorded. While lindane applications declined after that date, according to the temporal trend of the stable isomer of hexachlorocyclohexane (β-HCH), α-, and γ-HCH have been recorded at significant levels in the 2000s, suggesting first local post-ban applications. Nevertheless, the relationships between these OCPs and labile organic matter resulted in an overestimation of the post-ban releases. Also, the detection of stable metabolites of dichlorodiphenyltrichloroethane (DDT) (i.e. 4, 4′-DDE) and heptachlor (i.e. heptachlor epoxide) several decades after their ban, revealed the role of old deep soils erosion in the chronology of OCP releases and thus the reemergence of stable transformation products from historical OCPs. Graphical abstract: Image 1 Highlights: Lindane and aldrin showed temporal trends in link with their applications. Post-ban releases of HCHs and 4, 4′-DDE have been recorded. Temporal trends of OCPs showed significant links with labile or refractory OM. Recent releases of 4, 4′-DDE is due to former used of DDT and erosion of old soil. Normalized temporal trends showed an overestimation of post-ban releases of lindane.